Negotiating Tradition and Modernity: Seblang Bakunganin Banyuwangi 2011-2024 - Hervina Nurullita (Universitas Negeri Semarang, 2025)
This study aims to describe the meaning,development, and preservation efforts of theSeblang Bakungan tradition as one of the sacred rituals of theBanyuwangi community. This tradition has spiritual, social, and cultural values thatserve to maintain balance between humans, nature, and supernatural forces.The research uses historical methodswith data collection through interviews and documentation. The results of the researchshow that Seblang Bakungan is not just an art performance, buta sacred ritual rooted in the local belief system and plays an important rolein strengthening social solidarity in the community. The development of this traditionis influenced by social changes and the influence of tourism, but the communitycontinue to strive to preserve its authenticity and sacred values. Preservation effortsare carried out through the regeneration of practitioners, collaboration with local governments, andthe introduction of cultural values to the younger generation. This research confirmsthat Seblang Bakungan has a strategic role as a symbol of local cultural identityas well as a potential cultural tourism attraction that needs to be managed sustainably.